Rhabdomyolysis associated AKI: Case series from Iraq. - Al-Windawi, Suad; Ali, Ala (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Rhabdomyolysis is a clinical and biochemical syndrome that occurs when skeletal muscle cells disrupt and release creatine phosphokinase and myoglobin into the interstitial space and plasma. The causes of rhabdomyolysis are legion, but the most important and the classical form is the crush syndrome. Acute kidney injury occurs in 33-50% of patients with rhabdomyolysis. Here we report nine cases with acute kidney injury due to crush injury with rhabdomyolysis after the Al-Aema bridge catastrophe in Baghdad, in September 2005. Methods: Nine patients presented to the nephrology department of the Baghdad Teaching Hospital with a suggestive history of crush and laboratory evidence of rhabdomyolysis and acute kidney injury within the first three weeks of this tragic event. All patients were treated initially with aggressive fluid resuscitation with isotonic normal saline and bicarbonate. However, eight patients required acute peritoneal dialysis that was followed by intermittent hemodialysis, while only one received watchful conservative treatment with intravenous fluid support. Results: All patients achieved complete recovery of their clinical status and renal function and discharged within a period of 8 to 30 days. Conclusion: Crush syndrome is common. Early detection, aggressive fluid support still the main aspect of management. Correction of electrolytes abnormalities beside the judicious decision of dialysis initiation are also important in the management of this potentially life threatening situation.